THE ANALYSIS OF COMPARISON RESULTS USING EROSION AND OPENING ON THE PIAS CARD SEGMENTATION PROCESS (CASE STUDY: ST. BARONGAN) - Pujiastuti, Asih (Sekolah Tinggi Teknologi Adisutjipto, 2019)
This research was conducted to improve the application used in the calculation of the sunshine duration. The research that has been done using the opening method for segmentation of the pias card. The error or failure of segmentation is caused by a small burning object of the pias card and or a thin but translucent object, so that the object is partially lost or forms an object's separation area. Based on the error or failure of segmentation in the above research, the research will be done is to develop similar applications by replacing one of the methods with erosion morphology. The test was carried out with 92 data and the results stated that Erosion with Radius = 3 became the best alternative method in this research with RMSE 3.14.Keyword: segmentation, object, pias card,opening, erosion.